The Possible Contribution of the Amygdala to Memory - R. Babinsky; P. Calabrese; H. F. Durwen; H. J. Markowitsch; D. Brechtelsbauer; L. Heuser; W. Gehlen (Behavioural Neurology)
The processing of episodic memories is believed to depend on the proper functioning of so-called bottleneck structures through which information apparently must pass in order to be stored long term. These regions are seen in the basal forebrain, the medial diencephalon, and the medial temporal lobe. We here report a case with circumscribed bilateral temporal lobe damage, principally involving the amygdaloid area. Neuropsychological investigation demonstrated preserved intelligence, intact general memory and several other undisturbed cognitive functions, but a specific, affect-related, memory disorder. We conclude from these findings that the role of the amygdala is to process mnemonic events in a way that a specific emotional significance can be found and reactivated. Therefore it is suggested that the amygdala is likely to be a bottleneck structure for affect-related long-term memory functions.